LIMITATIONS ON VINATIC PRODUCTION (Plathymenia reticulata BENTH) FOR MINICUTTING - Gomes Lima Pessanha, Sara Edy (2018)
Vinatic (Plathymenia reticulata Benth.) is one of the native species of Brazil, of economic and environmental interest. Its propagation has been carried out by seeds, however, the difficult access to the matrices, long intervals of fruiting and difficulty of storage, emphasize the importance of techniques that allow the clonal propagation of the species. Studies conducted with vinatic minitumps, coming from seedlings have shown that although the ministumps show good sprouting, the minicutting rooting is very low. The aim of this study was to evaluate the production of vinatic seedlings by minicutting using different management to induce rooting. Two experiments were carried out in a greenhouse and, in the first experiment, the minitumps were obtained from seedlings produced from progenies of eleven matrices, from which the successive collection of minicuttings was promoted, these being submitted to different concentrations of the IBA growth regulator (0, 2.000, 4.000, 6.000 and 8.000 mg.L-1). In the second experiment, light management (shading at buds base and total shading of minitump) and nutrient were used, with nitrogen application (4 g.L-1 urea) in the minitumps. The minicuttings produced were evaluated for rooting capacity and anatomy at the base of the minicuttings. In the first experiment there was a variation of survival and tip pruning tolerance among the progenies of the matrices analyzed, with emphasis on progeny of the DOM matrix, which presented the highest survival percentage in the first collection (88,2%), and a sensitivity of NELI, ZE1 and ZE2 progenies to the management in the clonal minigarden. Vinatic responded positively to the successive collection of sprouts, with an increase in the number of sprouts produced from the fourth month of collection (210 days). There was no significant effect on rooting of vinatic plants when submitted to increasing concentrations of IBA, nor on the type of light and nitrogen management used to stimulate the minicuttings rooting. No anatomical barriers were observed to the rooting of the minicuttings in the different managements evaluated.